Effect of sigma E on carbapenem resistance in OXA-48-producing Klebsiella pneumoniae. (10th March 2022) - Cremanns, Martina; Lange, Felix; Gatermann, Sören G.; Pfennigwerth, Niels
Abstract: Objectives: Resistance levels of Gram-negative bacteria producing OXA-48 carbapenemase can vary greatly and some of them can even be categorized as susceptible to imipenem and meropenem according to EUCAST breakpoints. This study aimed to reveal resistance mechanisms leading to varying levels of resistance to carbapenems in Klebsiella pneumoniae with bla OXA-48 submitted to the German National Reference Centre for MDR Gram-negative bacteria. Methods: Meropenem-susceptible clinical bla OXA-48 -bearing K. pneumoniae isolates were put under gradually increasing selective pressure of meropenem. Clinical isolates and spontaneous meropenem-resistant mutants were whole-genome sequenced with Illumina and Oxford Nanopore Technology. Identified mutations apart from porin mutations were genetically constructed in the original clinical isolates using CRISPR/Cas. Clinical isolates and mutants were analysed for MICs, growth rates and expression of porins on mRNA and protein levels. Results: Mutations associated with meropenem resistance were predominantly found in ompK36, but in some cases ompK36 was unaffected. In two mutants, ISs within the rpoE (sigma factor E; σ E ) operon were detected, directly in or upstream of rseA . These IS 1R elements were then inserted into the same position of the susceptible clinical isolates using CRISPR/Cas. CRISPR-rseA-rseB-rseC mutants showed higher resistance levels to carbapenems and cephalosporins, reduced growth rates and reduced expression of major porins OmpK36 and OmpK35 in quantitative RT–PCR and SDS-PAGE. Conclusions: Enhanced synthesis of σ E leads to increased resistance to cephalosporins and carbapenems in clinical K. pneumoniae isolates. This effect could be based upon remodelling of expression patterns of outer membrane proteins. The up-regulated σ E stress response also leads to a significant reduction in growth rates.